Governance of Forests in India - Nigam, Bankim Chandra (Indian Forester, 2017)
Forests are one of the major contributors to the socio-economic development of a country like India. In this paper forest policy and governance of Indian forests have been reviewed from the available literature, interactions with stakeholders, public, researchers and administrators in allied fields. The analysis reveals that demands on Indian forests have increased tremendously and presently Indian forests are highly under pressure. This includes the demands of timber, non-timber, livelihood and that of carbon sequestration. The projected demand for timber by 2020, from the forests, is 153 million cubic meters (cu.m.) whereas the projected supply is only 60 million cu. m. The population of the country has increased from 45 billion in 1960 to 1329 billion (projected) in 2016. The policy and the system of governance of the forests of India, though have been modified from time to time but has not been geared for the drastic increase in the demand from the forests. Drastic changes in forest policy and governance of Indian forests with an infusion of research and inculcation of newer ideas are required if a genuine attempt is to be made towards achieving the demands of timber, non-timber, livelihood and that of carbon sequestration. On analysis, a hypothesis has been developed and some drastic policy and governance steps have been contemplated. They are detailed under these headings- increasing professionalism in the governance, especially at higher levels of administration, setting up an efficient forest statistical institution, creating a forestry knowledge hub by providing a conducive ecosystem for generation of knowledge that should involve private players along with government institutions and economic empowerment and management of the needs of stakeholders of the forests.